Dinamika Kesadaran Nasionalisme dalam Pembelajaran Sejarah: Perspektif Mahasiswa Pendidikan Sejarah di DKI Jakarta - Harinaredi Harinaredi; Didin Saripudin; Leli Yulifar; Helius Sjamsuddin (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Nationalism awareness is a vital component in history education, particularly in shaping students' national identity in the 21st century. This article aims to examine how history education students in DKI Jakarta perceive nationalism awareness through the dynamics of learning history. This study employs a qualitative approach using phenomenological methods. The participants involved are students from two higher education institutions: Universitas Muhammadiyah Prof. Dr. HAMKA (UHAMKA) and Universitas Negeri Jakarta (UNJ). Data were collected through in-depth interviews and thematic analysis. The findings indicate that nationalism awareness emerges not only from mastering historical content but also from reflective, contextual, collaborative, and technology-based learning approaches. Students actively interpret nationalism through class discussions, digital history projects, and reflections on the current national condition. This study concludes that 21st-century history learning should foster national values through pedagogical approaches that are creative, critical, and contextual, to remain relevant to the realities of today’s young generation.